ANALISIS SISTEM ON LOAD TAP CHANGER (OLTC) PADA TRANSFORMATOR 150/20 KV UNTUK MENJAGA KESTABILAN TEGANGAN PADA GI KALIWUNGU JAWA TENGA - Andy Rafianto (PSTE UNIMUS, 2019)
EnglishThe State electricity company (PLN) as a processor of electricity needs to provide electrical power services in accordance with the needs of consumers by providing power systems that have quality, continuity and high reliability, this can be achieved if the power system has a stable and constant voltage at a predetermined value. To maintain the output voltage on the secondary side of the transformer to remain constant at a value of 20 kV then use a tapping converter mounted on a 150/20kV power transformer and Work automatically on any voltage changes caused due to the voltage drop caused by the change of load and the length of the cable. The purpose of this research is to know the calculation step determines the change from (on load tap changer) to improve the secondary side voltage of power transformer 150/20 kV with the calculation of the output voltage of the transformer such as calculating the impedance value of the transformer, calculate the voltage drop across the transformer and calculate the output voltage of the transformer after the voltage on the secondary side of the transformer there is a decrease in the output voltage of the transformer beyond the specified setting, the next process is tap transfer according to tap settings. On the above calculation analysis then we will know whether the repeater is still below the standard SPLN (Attachment of the decision of the board of directors PLN) 72 1987 is the maximum voltage drop 5% on the secondary side.IndonesianPerusahaan Listrik Negara (PLN) sebagai pengolah kebutuhan listrik berusaha memberikan pelayanan ketenaga listrikan sesuai dengan kebutuhan konsumen dengan menyediakan sistem tenaga listrik yang mempunyai mutu , kontinuitas dan keandalan yang tinggi, hal ini dapat dicapai apabila sistem tenaga listrik mempunyai tegangan yang stabil dan konstan pada nilai yang sudah ditentukan. Untuk mempertahankan tegangan keluaran pada sisi sekunder transformator agar tetap konstan pada harga 20 kv maka digunakan pengubah sadapan yang dipasang pada transformator daya 150/20kV dan bekerja otomatis pada setiap perubahan tegangan yang disebabkan adanya jatuh tegangan karena adanya perubahan beban dan rugi hantaran. Tujuan dari penelitian ini adalah mengetahui langkah perhitungan menentukan perubahan on load tap changer dalam memperbaiki tegangan sisi sekunder transformator daya 150/20 kV dengan analisa perhitungan tegangan keluaran transformator diantaranya menghitung nilai impedansi trafo, menghitung drop tegangan pada trafo dan menghitung Vout transformator setelah mengalami drop tegangan, apabila tegangan keluaran transformator diluar setting yang telah ditentukan, selanjutnya dilakukan tahap pemindahan posisi tap pada trafo sesuai setting. Dengan analisa perhitungan diatas maka kita akan mengetahui apakah penyulang masih dibawah standar SPLN (Lampiran Surat Keputusan Direksi PLN) 72 1987 yaitu maksimal jatuh tegangan 5% pada sisi sekunder.